Protection of Children Against Sexual Abuse. Analysis of Indian Legislation from an International Perspective - Ahad, Safoora; D, Dr. Sankar (PRAWO i WIĘŹ, 2025)
Children are considered the backbone of any nation, and their well-being is one of the factors necessary for nation-building. Children are to be safeguarded from societal harms. They are granted the protection due to their vulnerable status, ensuring that they are not subjected to abuse. Their age and stage of development can pose various disadvantages and increase the risk of being harmed. Child sexual abuse (CSA) is a grave issue, but remains largely underestimated due to under-reporting, it has been happening from centuries CSA has only recently been publicly acknowledged as a serious problem around the world, including in India There are laws in India to address such perpetrators, and appropriate amendments have been made based on inputs from different segments of society. Despite the presence of existing laws, CSA in India has reached epidemic levels. The article examines Indian laws, specifically the IPC 1860, the POCSO Act 2012, and the BNS 2023, from an international perspective. It includes challenges on the key issues such as the “age of consent,” medical examination, and mandatory reporting in cases of child sexual abuse. The paper also assesses how well India has implemented the principles of the United Nations Convention on the Rights of the Child (UNCRC). It highlights the alignment of Indian laws with international standards, as well as the gaps.